The study of fracture phenomena and translational tipping deformation in M hard rock slopes - Sun, Wei; Ren, Xuhua; Lu, Chengao; Gao, Yiwei (Frontiers in Earth Science, 2025)
Tipping is characterized by the continuous rotation of blocks. The tipping deformations of high and steep hard rock slopes and steeply inclined layered slopes reveal that, under high in situ stress conditions, the formation process of high and steep slopes involves a strong release of horizontal stress. Depending on the specific geological conditions of the slope, additional loads may be provided to the block rotation deformation through traction or push mechanisms, causing slopes that do not originally meet the tipping conditions to exhibit tipping deformations. For hard rock tipping, the load level must be sufficient to cause the rock blocks to fracture and overcome the constraints of their own strength on rotational deformation, allowing the blocks to continue rotating. Thus, hard rock tipping involves two types of mechanical behaviors: macroscopic discontinuous deformation of the block boundaries and the continuous-discontinuous mesoscopic fracturing of the blocks themselves. Analytical solutions are no longer suitable for analyzing hard rock tipping deformation problems, necessitating the use of macroscopic-mesoscopic numerical methods that can simultaneously simulate discontinuous deformation of structural planes and rock block fracturing, such as UDEC-Voronoi simulation techniques. After analysis, it is necessary to meet two conditions: 1. To form an external load that can cause the rock to rotate continuously beyond its own weight; 2. The slope forms large structural planes on the steep slope, and the vertices of these structural planes have steep joints. The flexible use of UDC-Voronoi method improves the simulation accuracy and calculation efficiency.